2022
DOI: 10.3389/fped.2022.956227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and barriers to health care transition for adolescent patients with childhood-onset chronic diseases across Japan: A nation-wide cross-sectional survey

Abstract: Since the Japan Pediatric Society published its “Recommendations on Transitional Care for Patients with Childhood-Onset Chronic Diseases” in 2014, there has been an increased interest in the health care transition of adolescents with childhood-onset chronic diseases in Japan. However, the actual status of healthcare transition was not studied yet. The purpose of this study was to explore the prevalence of transitional support for adolescent patients with childhood-onset chronic disease and the factors hinderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, these adult patients often face complications possibly attributed to various factors such as age-related changes in therapeutic areas, poor treatment adherence and the development of other non-communicable diseases. In response, the Japan Pediatric Society published a consensus statement in 2014 titled “Proposal for Transitional Care for Patients with Childhood-Onset Diseases’’ based on the six core elements recommended by The American Academy of Pediatrics (AAP), The American Academy of Family Physicians (AAFP) and the American Board of Internal Medicine ( 12 ). The six core elements included: (i) establishing the transition policy; (ii) tracking and monitoring transition progress; (iii) assessing the patient’s readiness for transition; (iv) developing the transition plan with a medical summary; (v) transferring the patient; and (vi) completing the transfer and following up with patient and family ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these adult patients often face complications possibly attributed to various factors such as age-related changes in therapeutic areas, poor treatment adherence and the development of other non-communicable diseases. In response, the Japan Pediatric Society published a consensus statement in 2014 titled “Proposal for Transitional Care for Patients with Childhood-Onset Diseases’’ based on the six core elements recommended by The American Academy of Pediatrics (AAP), The American Academy of Family Physicians (AAFP) and the American Board of Internal Medicine ( 12 ). The six core elements included: (i) establishing the transition policy; (ii) tracking and monitoring transition progress; (iii) assessing the patient’s readiness for transition; (iv) developing the transition plan with a medical summary; (v) transferring the patient; and (vi) completing the transfer and following up with patient and family ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The six core elements included: (i) establishing the transition policy; (ii) tracking and monitoring transition progress; (iii) assessing the patient’s readiness for transition; (iv) developing the transition plan with a medical summary; (v) transferring the patient; and (vi) completing the transfer and following up with patient and family ( 13 ). However, to date, after a decade since the establishment of the consensus, Sakurai and colleagues reported that transition support was still limited due to various barriers involving patients, caregivers, and healthcare providers whereby only a few departments and individuals were dedicated to the transition process ( 12 ). To ensure synergy among the triad of relationships involving patients, caregivers, and healthcare providers, it is imperative to adopt a shared patient-centered and family-centered decision-making process among pediatric and adult teams to help make the transition process less stressful for patients and caregivers ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transition to adulthood is recognized as a complicated process for youth in general and more so in those with special health care needs ( 2 , 3 ). While moving toward adulthood, adolescents with special health care needs must learn how to self-manage their medical needs as well as face an imminent shift in service location.…”
Section: Introductionmentioning
confidence: 99%